2002
DOI: 10.1590/s0074-02762002000300031
|View full text |Cite
|
Sign up to set email alerts
|

Oral Susceptibility to Yellow Fever Virus of Aedes aegypti from Brazil

Abstract: The oral susceptibility to yellow fever virus was evaluated in 23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 7 publications
0
27
2
2
Order By: Relevance
“…albopictus increase the threat of urbanization of yellow fever transmission in South America. 32 Our results showed that Brazilian Ae. albopictus were as efficient as North American populations in being infected with dengue and yellow fever viruses.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…albopictus increase the threat of urbanization of yellow fever transmission in South America. 32 Our results showed that Brazilian Ae. albopictus were as efficient as North American populations in being infected with dengue and yellow fever viruses.…”
Section: Discussionmentioning
confidence: 54%
“…27 Aedes albopictus in North America has been shown to be an efficient experimental vector of dengue viruses 28,29 and yellow fever virus. 28 In this study, we addressed the following questions: 1) 32 The titer used in the infectious meal was 10 8.7 MID 50 /mL. Experimental infection of F 1 females and statistical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus, Lourenço-de-Oliveira et al (2003) estimated that infection rates for dengue were mostly between 50 and 80%, although infection rates have varied from 22.5 to 71.4% in four of their samples from Rio de Janeiro. These divergences are probably due to differences in experimental conditions, specially the number of generations of mosquitoes used, the method of virus titration and virus titer in the infectious blood meal, as demonstrated before (Vazeille et al 2002). Indeed, Lourenço-deOliveira et al (2003) used a distinct method of virus titration and a much higher virus titer (10 8.2 MID50; where MID50 is 50% mosquito infectious dose) than ours (10 6 TCD50) for mosquito infection.…”
Section: Discussionmentioning
confidence: 71%
“…aegypti populations depend on colonization history and may be associated with susceptibility to DENV-2. Lourenço-de-Oliveira et al (2002) demonstrated the Brazilian populations of Ae. aegypti to be heterogeneous to susceptibility to both the YFV and DENV-2 infection.…”
Section: Discussionmentioning
confidence: 97%